(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the decision making power of women in their married family life specially regarding family planning. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Department of Community Medicine, Foundation University Medical College, Rawalpindi from 1st April to 31st Oct, 2014. Materials and Methods: Two hundred households were selected through simple random sampling technique and data was collected from women in each house, married at least for two years, using a self- administered structured questionnaire translated in Urdu language, and assessed using SPSS 19. Results: Women were found to have a little say in decision making about the food preparation (37.5%), household purchase (25%), medical treatment (4.1%), working outside (5.2%), family planning consultation(40%) , number of children (3.7%), contraception techniques(15.4%), tubal ligation(9.4%) , circumcision of sons (1.9%), aqeeqa ceremony (2.2%)deciding about the place of delivery (52.1%).Almost 47.6% were pressurized by in-laws in decision making about family planning techniques. Conclusion: The study revealed that in-laws, had a major influence on the decision-making of women specially regarding family planning. Hence interventions need to be implemented to raise women empowerment by involving in-laws in health education campaigns